Research status and hotspots of medication safety in older adults: A bibliometric analysis - Xie, Chuantao; Gu, Yanhong; Wang, Yanan; Ni, Feixia; Li, Yumei (Frontiers in Public Health, 2023)
Background Medication safety is a significant concern in healthcare. Research on medication safety for older adults has taken a broad approach, resulting in a range of proposals. At this juncture, it is necessary to identify the main contributors and establish the current developmental status of the principal research topics. Objective This study sets out to summarize the state-of-the-art in medication safety for older adults, identifying significant achievements, key topics, and emerging trends. Methods The Web of Science Core Collection (WOSCC) database was searched for relevant documentation over the interval 1st January 2000 to 31st December 2021. Annual outputs and citations were identified from the WOS citation reports. CiteSpace and VOSviewer were adopted for bibliometric analysis and visualization that included the distribution of countries/regions, organizations, authors and journals, and an analysis of co-cited references and keywords. Results A total of 1,638 documents were retrieved for bibliometric analysis, yielding 34.29 citations per document. Publications have increased over the past two decades, reaching 177 outputs in 2019. Our database encompasses 71 countries/regions, 2,347 organizations, and 7,040 authors. The United States ranks first in terms of scientific activity with 604 publications (36.87%). We have identified the University of Sydney as the most prolific organization (53 publications). J. T. Hanlon, J. H. Gurwitz, D. O'Mahony, and G. Onder are the most influential researchers in terms of publications and citations. The Journal of the American Geriatrics Society ranks first with 89 (5.43%) papers. In terms of major research directions, three topics have been identified from co-cited reference and keyword analysis: (1) estimation of the prevalence and variables associated with polypharmacy and potentially inappropriate medication; (2) analysis of interventions involving pharmacists and the associated impact; (3) patient experience and perception associated with medication use or pharmaceutical care. Conclusion Research on medication safety for older adults has progressed significantly over the past two decades. The United States, in particular, has made important contributions to this field. Polypharmacy and potentially inappropriate medication use, interventions involving pharmacists, patient experience and perception represent the current focus of research. Our findings suggest that these directions will continue as research hotspots in the future.